2004
DOI: 10.1007/s00467-003-1378-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone histology in steroid-treated children with non-azotemic nephrotic syndrome

Abstract: Patients with nephrotic syndrome (NS) and normal glomerular filtration rate (GFR) frequently exhibit abnormalities of calcium and vitamin D homeostasis, mainly hypocalcemia and reduced circulating vitamin D metabolites. These abnormalities have been linked to alterations of bone histology in adults with non-azotemic NS, particularly osteomalacia and excessive bone resorption. Whether similar abnormalities of bone histology occur in children and adolescents with NS, particularly in those requiring prolonged tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…When appropriate corrections for body size are employed, the literature has been consistent on documenting a negative impact of steroid exposure on bone health in children with NS [21, 22]. Studies utilizing bone biopsy data have demonstrated abnormalities in the bones of children with NS treated with steroids, including increased focal osteomalacia and bone resorption relative to controls [30]. Recently, Choudhary et al performed an interventional trial in children with new-onset NS, which showed that children with incident disease had abnormalities in bone mineral content at 12 weeks, and supplemental calcium and vitamin D were protective against these bone abnormalities [24].…”
Section: Discussionmentioning
confidence: 99%
“…When appropriate corrections for body size are employed, the literature has been consistent on documenting a negative impact of steroid exposure on bone health in children with NS [21, 22]. Studies utilizing bone biopsy data have demonstrated abnormalities in the bones of children with NS treated with steroids, including increased focal osteomalacia and bone resorption relative to controls [30]. Recently, Choudhary et al performed an interventional trial in children with new-onset NS, which showed that children with incident disease had abnormalities in bone mineral content at 12 weeks, and supplemental calcium and vitamin D were protective against these bone abnormalities [24].…”
Section: Discussionmentioning
confidence: 99%
“…Adults with rheumatoid arthritis have been shown to have evidence of decreased trabecular bone volume and turnover [15, 35]. Reduced trabecular thickness and osteoblast surface have similarly been found in other cohorts of children treated with glucocorticoids such as those with Duchene muscular dystrophy and steroid dependent nephrotic syndrome [21, 22]. Unlike, however, the histomorphometry results from the pediatric patients with nephrotic syndrome, our subjects did not have evidence of osteomalacia, as seen by the reduced osteoid thickness and volume.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of bone histomorphometry and mineralization in pediatric patients treated with glucocorticoids have contributed to the understanding of underlying pathology and clinical factors with the potential to predict severity of bone disease [21, 22]. Given these features have not to date been described in pediatric rheumatalogical patients, the aims of this pilot study were therefore to characterize bone histomorphometry and mineralization in a small cohort of children with rheumatic diseases and to assess associations between clinical and radiological indices to bone micro-architecture.…”
Section: Introductionmentioning
confidence: 99%